2021
DOI: 10.7150/ijms.52104
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of bone marrow mesenchymal stem cells in a stressed environment - Comparison with osteocyte cells

Abstract: Introduction: Recently, the efficacy of mesenchymal stem cells (MSCs) mediated by their tissue repair and anti-inflammatory actions in the prevention and therapy of various disorders has been reported. In this research, our attention was focused specifically on the prevention and therapy of glucocorticoid-induced osteonecrosis. We investigated the stress resistance of MSC against glucocorticoid administration and hypoxic stress, which are factors known to induce osteocytic cell death. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Mitochondrial dysfunction can affect osteoblast, osteocyte, and vascular endothelial cell functions ( 69 , 70 ) as well as inflammatory reactions in chondrocytes. In turn, this leads to metabolic disorders in chondrocytes, affecting endochondral osteogenesis ( 71 ).…”
Section: Mechanism Of Abnormal Bone Defect Repair In High-altitudementioning
confidence: 99%
“…Mitochondrial dysfunction can affect osteoblast, osteocyte, and vascular endothelial cell functions ( 69 , 70 ) as well as inflammatory reactions in chondrocytes. In turn, this leads to metabolic disorders in chondrocytes, affecting endochondral osteogenesis ( 71 ).…”
Section: Mechanism Of Abnormal Bone Defect Repair In High-altitudementioning
confidence: 99%
“…SANFH is a complex pathological process in which various factors lead to intramedullary microvascular lesions, affecting the blood and oxygen supply of the femoral head and ultimately causing hypoxia in the necrotic area [14][15][16][17] . The hypoxia apoptosis of transplanted BMSCs in the osteonecrotic area limits the transplantation efficacy of BMSCs 12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the transplanted BMSCs display high levels of apoptosis in the osteonecrotic area in vivo, which limits the transplantation efficacy 12,13 . The apoptosis of transplanted BMSCs is mainly related to the local hypoxic microenvironment in the necrotic area of the femoral head [14][15][16][17] . There is still a lack of effective intervention methods for hypoxia-induced apoptosis of transplanted BMSCs.…”
mentioning
confidence: 99%
“…In recent years, the utilization of MSC-based strategies in the treatment of multiple myeloma has drawn much attention [ 17 , 28 30 ]. Shimasaki and colleagues found that the survival rate of MSCs is maintained after treatment with dexamethasone [ 31 ], indicating the resistance of MSCs to dexamethasone. However, it is still unclear whether MSCs had an impact on dexamethasone-mediated multiple myeloma therapy.…”
Section: Discussionmentioning
confidence: 99%